2015
DOI: 10.14202/vetworld.2015.350-357
|View full text |Cite
|
Sign up to set email alerts
|

Impact of second line limiting amino acids’ deficiency in broilers fed low protein diets with rapeseed meal and de-oiled rice bran

Abstract: Aim:To study the impact of deficiency of second line limiting amino acids (SLAA; valine, isoleucine and tryptophan) on the production performance and carcass characteristics of commercial broilers.Materials and Methods:A control (T1) corn-soy diet was formulated to contain all essential AA on standardized ileal digestible basis; While in T2-a ‘moderate SLAA deficit’ diet was formulated by replacement of soybean meal with 6% rapeseed meal and T3-a ‘high SLAA deficit’ diet was formulated by replacement of soybea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 22 publications
2
2
0
Order By: Relevance
“…The deficiencies of various amino acid viz ., valine (Corzo et al, 2011), valine and isoleucine (Corzo et al, 2009) and valine, isoleucine and tryptophan on DORB based rations (Basavanta Kumar et al, 2015) have been shown to depress feed efficiency similar to present study. The protein factor with a reduction of 1.5% unit protein and supplementation of limiting amino acids resulted in significant depression of FCR at all production phases, while, 0.75% unit protein reduction significantly reduced FCR only during pre-starter phase.…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…The deficiencies of various amino acid viz ., valine (Corzo et al, 2011), valine and isoleucine (Corzo et al, 2009) and valine, isoleucine and tryptophan on DORB based rations (Basavanta Kumar et al, 2015) have been shown to depress feed efficiency similar to present study. The protein factor with a reduction of 1.5% unit protein and supplementation of limiting amino acids resulted in significant depression of FCR at all production phases, while, 0.75% unit protein reduction significantly reduced FCR only during pre-starter phase.…”
Section: Resultssupporting
confidence: 85%
“…Among amino acid, methionine is primarily required for initiation of protein synthesis and has been revealed to influence myogenic gene expression in broilers (Wen et al, 2014) and moreover, lysine, methionine, threonine, valine and isoleucine are components of muscle protein and their deficiency invariably reduced the BWG. The growth retardation as a result of deficiency of either individual or various combinations of limiting amino acids lysine, methionine, threonine, valine, isoleucine and tryptophan is well noticed in previous studies (Corzo et al, 2009; Corzo et al, 2011; Basavanta Kumar et. al., 2015).…”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…Valine is considered the fourth limiting amino acid after Met, Lys, and Thr in vegetable diets when considering live weight gain in birds (Rostagno et al., 2011). When diets are formulated with low protein levels, isoleucine becomes co-limiting with Val, notwithstanding feed supplementation with Lys, Met, and Thr (Corzo et al, 2007; Kumar et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Valine is 4 th amino acid in corn and soybean meal-based diets (Baker et al 2002;Corzo et al 2007Corzo et al , 2009Rostagno et al 2011). Valine deficiency in broilers may result in reduced growth performance, carcass quality and immune response (Kumar et al 2015;Nascimento et al 2016;Kaplan and Yildiz, 2017) respectively. Studies have been conducted on dietary supplementation of L-valine in broilers performance (Corzo et al 2007;Azzam et al 2015) but such studies are lacking in turkeys.…”
Section: Introductionmentioning
confidence: 99%